What Matters Most for Equity and Inclusion in Education Systems : A Framework Paper - Wodon, Quentin (World Bank, Washington, DC, 2017)
The purpose of systems approach for better education results (SABER) - equity and inclusion (E and I) is to help countries ensure that all children go to school and learn. This paper is part of a suite of what matters papers published under the SABER initiative. SABER was launched by the World Bank to help governments systematically examine and strengthen the performance of their education systems so that all children and youth can be equipped with knowledge and skills for life. SABER is organized around a dozen different domains that collect data on country policies in education. This paper is about E and I in education systems. The paper first provides a quick diagnostic of where countries stand in terms of E and I; why E and I matters for the eradication of extreme poverty, shared prosperity, and development; and how the SABER E and I domain is structured. Three policy goals are then emphasized for E and I in education and discussed in subsequent respective chapters: (1) establishing an enabling environment and providing resources needed for an education system to be equitable and inclusive; (2) providing general conditions that enable all children to start school ready to learn and remain in school; and (3) ensuring that all children, especially vulnerable groups of children, learn in school.